A study on physical and geochemistry behavior of artificial organic soils [electronic resource] - Nur Aqmalina Rusli, 1988-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011